EMPOWERMENT OF WOMEN IN MAGADH- A NAXAL AFFECTED REGION - singh, Nisha (Innovative Research Thoughts, 2018)
For centuries women were not treated equal to men in many ways. They were not allowed to own property, they did not have a share in the property of their parents, they had no voting rights, and they had no freedom to choose their work or job and so on. Gender inequality has been part and parcel of an accepted male-dominated Indian society throughout history. Women were expected to be bound to the house, while men went out and worked. The traditional Indian mentality assumes that the place of women is mainly concentrated to the household activities like kitchen work and upbringing of the children. There is systematic discrimination against women economically, socially, politically and culturally more so, in India. These discriminations & disabilities are practiced at all levels day in & day out. Bihar has always been a disastrous place for women making them suffer by keeping them away from education, job, business, limited social activities and they are even affected by the extremists’ activities. Women in Magadh region faces even the darker side of the above mentioned facts. They are in continuous fear of naxals. They women in this region are weak on both educational and political grounds. In this paper, all these issues and challenges are discussed for extracting an idea for empowering women.